The Interplay Among AI, Language Research, and Academic Publishing: A Systematic Review of Trends and Future Directions - Tatipang, Devilito P.; Pontillas, Marlon S.; Alrajafi, Gali; Rovikasari, Mala; Ndruru, Falentinus (English Education Department, 2024)
The transformative role of Artificial Intelligence (AI) in language research and academic publishing has garnered significant attention in recent years. This systematic review explores the interplay among AI, language research, and academic publishing, focusing on trends, challenges, opportunities, and future directions. A total of 30 peer-reviewed articles published between 2020 to 2024 were analyzed using PRISMA guidelines to ensure comprehensive coverage. Findings reveal that AI technologies such as Natural Language Processing (NLP), machine translation, and automated peer-review systems are revolutionizing methodologies in linguistic studies and scholarly dissemination. While the adoption of AI presents numerous opportunities such as enhanced accessibility, increased efficiency, and advanced linguistic analysis it also raises challenges. Key concerns include ethical issues, data privacy, biases in AI algorithms, and resistance to adoption due to fears of over-reliance on automation. Additionally, the future of AI in these domains points to exciting possibilities, including ethical AI development, generative AI’s role in redefining authorship, and the integration of AI literacy into academic training. This review contributes to the growing discourse by mapping current trends and identifying gaps in research, offering actionable recommendations for stakeholders. It underscores the need for responsible and inclusive AI practices to harness its potential fully, ensuring sustainable advancements in language research and academic publishing.